Keberlanjutan Peran Dukungan Sebaya di Dalam Sistem Penanggulangan HIV di Tingkat Provinsi dan Kota/Kabupaten Indonesia - Handayani, Sarah; Mardhiati, Retno (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2018)
Background: Role of peer group support is one of important role in HIV/AIDS prevention system. Peer group can be implemented contiiously if sustainability program factors exist. Aim of Study:This study aimed to assess factors which effect peer group support sustainability in HIV/AIDS eradication both in district and provincial level. Method: The study collected qualitative data and literature review. Indepth interview was conducted to key informants. Result. Peer group support can be implemented in HIV/AIDS eradication system since factors that effect were developed. Those factors were 1) Internal factor includes group motivation, leadership, self help and group accountability. 2) External Factor includes participatory in HIV/AIDS eradication system, access to resources and referral system.